Differences in physical fitness among indoor and outdoor elite male soccer players - Gorostiaga, E. M.; Llodio, I.; Ibanez, J.; Granados, C.; Navarro, I.; Ruesta, M.; Bonnabau, H.; Izquierdo, M. (European Journal of Applied Physiology, 2009)
This study compared anthropometric (body height, body mass, percent body fat, fat-free body mass) and physical fitness characteristics (vertical jump height, power-load curve of the leg, 5 and 15 m sprint running time and blood lactate concentrations ([La]b) at submaximal running velocities) among 15 elite male indoor soccer (IS) and 25 elite male outdoor soccer (OS) players. IS players had similar values in body height, body mass, fat-free body mass and endurance running than OS players. However, the IS group showed higher (P < 0.05-0.01) values in percent body fat (28%) and sprint running time (2%) but lower values in vertical jump (15%) and half-squat power (20%) than the OS group. Significant negative correlations (P < 0.05-0.01) were observed between maximal sprint running time, power production during half-squat actions, as well as [La]b at submaximal running velocities. Percent body fat correlated positively with maximal sprint time and [La]b, but correlated negatively with vertical jump height. The present results show that compared to elite OS players, elite IS players present clearly lower physical fitness (lower maximal leg extension power production) characteristics associated with higher values of percent body fat. This should give IS players a disadvantage during soccer game actions.